Effect of cognitive load and working memory capacity on the efficiency of discovering better alternatives: A survival analysis - Ninomiya, Yuki; Iwata, Tomoyuki; Terai, Hitoshi; Miwa, Kazuhisa (Memory & Cognition, 2024)
Why do humans attempt to discover better alternatives to solve a problem even when they know the way to solve it? This question is related to the flexibility of thinking and is the subject of studies on the Einstellung effect. This study focuses on cognitive load for familiar trained procedure as a factor that influences the discovery of alternatives in Einstellung situations, where the problem can be solved using a trained procedure. Many studies on creative problem solving and strategy selection demonstrate that cognitive load for facilitates the discovery of alternatives. However, findings are inconsistent regarding Einstellung situations. We argue that the reason for such inconsistent results were the use of manipulations such as the double task, which both load on the trained and alternative procedure and the lack of perspective on efficiency in analysis. Therefore, we examine the relationship between cognitive load manipulated by the complexity of the trained procedure and time-based performance measured by the number of trials prior to finding alternatives. The results illustrate that higher cognitive load increased the efficiency of discovery of alternatives and that this effect was significant for participants with high working memory capacity. This study provides empirical evidence that high cognitive load for trained procedure facilitates the discovery of alternatives and suggests the importance of considering temporal properties, such as efficiency, when examining the effects of working memory on problem solving, which requires cognitive flexibility.